2011
DOI: 10.1371/journal.pone.0019927
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the CD95-Induced Apoptosis: The Role of CD95 N-Glycosylation

Abstract: Protein modifications of death receptor pathways play a central role in the regulation of apoptosis. It has been demonstrated that O-glycosylation of TRAIL-receptor (R) is essential for sensitivity and resistance towards TRAIL-mediated apoptosis. In this study we ask whether and how glycosylation of CD95 (Fas/APO-1), another death receptor, influences DISC formation and procaspase-8 activation at the CD95 DISC and thereby the onset of apoptosis. We concentrated on N-glycostructure since O-glycosylation of CD95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 55 publications
4
48
0
1
Order By: Relevance
“…Fas receptor is also expressed as N-glycosylated proteins (García-Fuster et al, 2003;Kamitani et al, 1997), and KA (at 72 h) increased its content in the hippocampus, an effect somewhat opposite to that of Fas aggregates. Interestingly, N-glycosylation of Fas receptor was shown to reduce pro-caspase-8 activation (Shatnyeva et al, 2011), which is in line with p18 fragment downregulation reported in the present study. A recent investigation has also revealed the important role played by Fas receptor (mRNA) in KA-induced hippocampal neuronal death in mice (Ettcheto et al, 2014), but this study did not quantify the status of Fas receptor protein forms.…”
Section: Discussionsupporting
confidence: 92%
“…Fas receptor is also expressed as N-glycosylated proteins (García-Fuster et al, 2003;Kamitani et al, 1997), and KA (at 72 h) increased its content in the hippocampus, an effect somewhat opposite to that of Fas aggregates. Interestingly, N-glycosylation of Fas receptor was shown to reduce pro-caspase-8 activation (Shatnyeva et al, 2011), which is in line with p18 fragment downregulation reported in the present study. A recent investigation has also revealed the important role played by Fas receptor (mRNA) in KA-induced hippocampal neuronal death in mice (Ettcheto et al, 2014), but this study did not quantify the status of Fas receptor protein forms.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas TRAIL bears two potential O-glycosylation sites, 18 Fas contains two N-glycosylation sites. 21 In the presence of Fas ligand, Fas-associated N-glycans contribute to stabilize the core DISC structure, DISC-DISC interactions and procaspase-8 oligomerization 21 ( Figure 1b). By contrast, when Fas is aberrantly glycosylated because of localization of the protein tyrosine phosphatase SHP-1 in the endoplasmic reticulum (ER), Fas fails to oligomerize in response to Fas ligand and T-cell homeostasis is impaired.…”
Section: Glycans Exposed On Death Receptors Control Cell Deathmentioning
confidence: 99%
“…These high-molecular-weight bands represent sialylated and glycosylated Fas (supplemental Figure 5) as previously reported. 32,33 Fas glycosylation does not alter apoptosis sensitivity, 31,32 thus the observed changes do not interfere with our functional studies.…”
Section: Blood 6 June 2013 X Volume 121 Number 23 Surface Nucleolinmentioning
confidence: 69%